Optimalisasi Penilaian Berbasis Kelas dan Pengembangan Tes untuk Meningkatkan Literasi Siswa SDIT Wadi Fatimah Cirebon - Ade Like Rachmawati; Aminnudin Aminnudin; Kartimi Kartimi (PT Barkah Ilmi Fiddunya, 2024)
The problem of education quality in Indonesia is still a concern, as seen from the results of TIMSS and the PERC survey which showed a low ranking compared to other countries in Southeast Asia. One of the fundamental problems is the low level of literacy of elementary school students, which is caused by inappropriate teaching methods, irrelevant teaching materials, and assessment approaches that have not been integrated with learning. This study aims to improve the effectiveness of the implementation of class-based assessment (CBA) and the development of contextual literacy tests in improving student literacy at SDIT Wadi Fatimah. The study used a qualitative descriptive approach with data collection techniques through analysis, observation, document studies, and literacy test results. The data analysis process was carried out using the Miles and Huberman model, namely data reduction, data presentation, and drawing conclusions. The study showed that the implementation of CBA and the development of literacy tests based on Islamic values ​​significantly improved students' literacy skills. The average student literacy score increased from 68.5 in the first cycle to 82.3 in the second cycle. In addition, students' active participation in reading and creative writing activities increased by 40%. This study recommends that other educational institutions adopt PBK strategies and contextual test development to improve the quality of student literacy. Teachers also suggest integrating local or religious values ​​into teaching to create relevant and meaningful learning. This effort is expected to support the formation of a superior, characterful, and competitive generation